Determinants of Transport Costs for Inter-regional Trade - Se-il Mun; Yoko Konishi; Yoshihiko Nishiyama; Ji-eun Sung (European Regional Science Association (ERSA), 2013)
Our paper empirically investigates the structure of transport costs for interregional trade, by using the micro-data of freight charge. We focus on road transport, reflecting the fact that trucking has a dominant share in transporting goods between regions in many countries (in Japan, 91.2% of overall domestic freight volume in 2005). An advantage of our method is that our data represent the costs actually incurred by shippers or carriers, unlike those based on indirect information, or constructed data. Another feature of our paper is to consider the cost structure of each shipment. This is in contrast to many other studies using firm-level data. We present a microeconomic model of inter-regional freight transportation based on careful formulation of cost structure in trucking firm and market equilibrium. We consider that output of transportation service is a bundle of multiple characteristics, such as distance (d), volume (q) and time (t). This is different from the conventional definition of output variable in transportation, i.e., the product of quantity and distance (q*d, according to the above notations). We derive the freight charge equation for empirical analysis based on the market equilibrium, which is derived in a similar manner to the hedonic theory. We use the micro-data from the 2005 Net Freight Flow Census (NFFC), in which information on freight charge and other variables for individual shipment (origin, destination, volume, shipping time) are obtained. The data for other explanatory variables such as distance, toll payment and wage are obtained from various sources. By estimating the parameters of freight charge equation, we investigate the effects of various factors on the level of freight charge. We also examine the existence of scale economies with respect to lot size (weight) and long-haul economies: transport cost per unit weight is decreasing with weight; transport cost per distance is decreasing with distance. Main results are summarized as follows. (1) There are very strong scale economy and long-haul economy: elasticity of freight charge with respect to lot size and distance evaluated around the sample mean are -0.55 and 0.60, respectively. Consequently, the unit freight charges have similar values if the values of q*d are the same. This suggests that the conventional definition of output, ton km, turns out to be a good approximation. (2) Degree of market competition (represented by the number of trucking firms per 1000 population) has significant effect on freight charge: elasticity is 0.09.
Keywords: 330; transport cost; inter-regional trade; freight charge; Scale economy; long-haul economy